A second mutation in the methylenetetrahydrofolate reductase gene and the risk of venous thrombotic disease - Franco, R. F.; Morelli, V; Lourenco, D.; Maffei, Francisco Humberto de Abreu [UNESP]; Tavella, M. H.; Piccinato, C. E.; Thomazini, I. A.; Zago, M. A. (Blackwell Science, 1999)
We assessed the effect of a recently described mutation in the MTHFR gene (1298 A --> C) on the risk of deep venous thrombosis (DVT) by determining its prevalence in 190 patients with verified DVT and in age-, race- and gender-matched controls. MTHFR 1298 A --> C was found in 42.1% of patients and in 41.1% of controls. The OR for venous thrombosis was 1.07 (95% CI 0.70-1.65) for heterozygotes and 0.83 (95% CI 0.33-2.08) for homozygotes. The OR for the factor V Leiden (FVL) mutation was 3.40 (95% CI 1.22-9.48), for FII 20210 G --> A was 5.22 (95% CI 1.12-24.2) and for MTHFR 677 C --> T, 1.24 (95% CI 0.82-1.87). No significant increased risk for venous thrombosis was found when MTHFR 1298 A --> C was coinherited with FVL (OR 2.85, 95% CI 0.88-9.23), FIT 20210 G --> A (OR 7.19, 95% CT 0.87-59.4) or MTHFR 677 C --> T (OR 1.44, 95% CT 0.71-2.92). These data do not support a critical role of MTHFR 1298 A --> C in the predisposition to DVT.
Keywords: MTHFR 1238 A -> C; MTHFR 677 C -> T; thrombosis; risk factor; mutation